2011
DOI: 10.1016/j.ijid.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli septic arthritis of a lumbar facet joint following urinary tract infection

Abstract: Septic arthritis of a lumbar facet joint is a rare condition. We report the case of a 77-year-old diabetic woman who developed fever and back pain 15 days after she had been diagnosed with a genitourinary infection for which she had received ciprofloxacin. Physical examination showed fever (38°C) and pain on pressure over the lower lumbar spinous vertebral apophyses and over the lower left paraspinal musculature. Investigations showed a white cell count of 8.4×10⁹/l, neutrophils 85.3%, erythrocyte sedimentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
0
11
0
6
Order By: Relevance
“…Herrero et al reported a case of E . coli as a causative organism for septic arthritis of lumbar facet joint following a urinary tract infection [17] . Blood cultures are usually positive in 50% of cases [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Herrero et al reported a case of E . coli as a causative organism for septic arthritis of lumbar facet joint following a urinary tract infection [17] . Blood cultures are usually positive in 50% of cases [11] .…”
Section: Discussionmentioning
confidence: 99%
“…However, spinal MRI has facilitated the diagnosis of FJA regardless of a septic or non-septic condition. The most common cause of FJA is bacterial hematogenous dissemination from a distant focus of infection, such as acute pyelonephritis (4). Non-septic FJA has been reported to occur due to cartilage damage associated with osteoarthritis and crystal-induced arthritis as CPPD disease.…”
Section: Discussionmentioning
confidence: 99%
“…Pyogenic facet joint (PFJ) is found in 4% of all hematogenous pyogenic infections of the spine and is associated with concurrent extraspinal infection, diabetes mellitus, liver disease, end-stage renal disease, morbid obesity, intravenous drug abuse, alcohol abuse, and chronic steroid use [6, 10]. Other etiologies reported are infective endocarditis [2], acupuncture treatment [1], urinary tract infection [4], and facet injections [5, 7]. Patients commonly present with acute onset of back pain, radiculopathy, fever or paresis.…”
Section: Discussionmentioning
confidence: 99%
“…Associated inflammatory changes in the epidural space or adjacent paraspinal muscles can be distinguished with gadolinium-enhanced T1-weighted MRI. Gallium-67 scintigraphy can be used when MRI is contraindicated and has good sensibility and sensitivity [4].…”
Section: Discussionmentioning
confidence: 99%